As metáforas zoomórficas na Revista Capricho - Araújo, Ediliane Brito de (2004)
Recent researches suggest that metaphor should not be considered just as a resource of poetic imagination or a rhetoric figure, because it is present in our routine lives, not only associated to the language but in our thoughts and actions. This research tries to highlight the pertinences of zoomorphic metaphors found in Capricho magazine sample as element that prove and spreads the declassification of the female subject. For this research, launched the following hypotheses: 1) the zoomorphic metaphors represent types of reduction of feminine sexuality; 2) this kind of metaphors are bodily lived; 3) prejudiced and stereotyped points of views like these are reinforced by the media whenever they´re used; 4) the advertisement of zoomorphic metaphors are found related to discipline. It is believed to help explain how the language reflects the socials levels thinking, as favor the point of view of those who chooses this kind of magazine as reading material. In this gender studious regard, information was researched, in authors like: Almeida (2002), Louro (1995;1998), Pires (2002), Scott (1995), Strey (1998;1999), among others. The research looks basically for positive bases, approaching the issue power in the ideas of Foucault (2002; 2001), and in the ideas of Lakoff & Johnson (2002) to research about metaphors.